Consciousness & emotion : agency, conscious choice, and selective perception - Ellis, Ralph D.; Newton, Natika (Consciousness & emotion ;, 2005)
The papers in this volume of Consciousness & Emotion Book Series are organized around the theme of "enaction." Enactive emotional processes are not merely the recipients of information or the passive victims of input and learning. The organism first is engaged in an ongoing, complex pattern of self-organizational activity, for the purpose of maintaining a dynamical continuity of pattern across changes of subserving micro-constituents and environmental conditions, making use of multiple shunt mechanisms, feedback loops, and other complex dynamical features. Self-organizational structure is used